Impact of Pre-procedural Cerebrovascular Events on Clinical Outcomes After Transcatheter Aortic Valve Implantation in Patients with Severe Aortic Stenosis - Wiktorowicz, Agata; Kleczynski, Pawel; Dziewierz, Artur; Tokarek, Tomasz; Sorysz, Danuta; Bagienski, Maciej; Rzeszutko, Lukasz; Dudek, Dariusz (Current Pharmaceutical Design, 2018)
Background: Transcatheter aortic valve implantation (TAVI) is an increasingly common treatment of symptomatic severe aortic valve stenosis (AS). Thus, it is reasonable to carefully investigate the impact of individual clinical factors on outcomes after TAVI. Objectives: We aimed to investigate the impact of the previous cerebro-vascular events (CVEs) on outcomes of patients with severe AS undergoing TAVI. Methods: A total of 148 consecutive patients scheduled for TAVI were included and stratified as with and without a history of CVEs (stroke or transient ischemic attack). Frailty features were also assessed. The primary endpoint was a 12-month all-cause mortality. Results: Seventeen (11.5%) patients had a history of CVEs (the CVE group). At 30 days and 12 months, all-cause mortality was higher in the CVE group [30-day: 5 (29.4%) vs. 7 (5.3%); p=0.005; 12-month: 9 (52.9%) vs. 13 (9.9%); p=0.001]. Similarly, at the longest available follow-up, mortality was higher in the CVE group [10 (58.8%) vs. 23 (17.6%); p=0.001]. Similar rates of other complications after TAVI were noted, apart from inhospital acute kidney injury (AKI) grade 3 [3 (17.6%) vs. 5 (3.8%); p=0.049] and blood transfusions [9 (52.9%) vs. 35 (26.7%); p=0.026]. Results of 5MWT and Katz index assessment indicated a greater level of frailty in the CVE group. There were no differences in subsequent events including CVEs, bleeding, myocardial infarction, and new-onset of atrial fibrillation (AF) at 12 months between the groups. Conclusion: We showed that a history of CVEs in patients with severe AS undergoing TAVI is associated with a higher long-term mortality.
Keywords: transient ischemic attack